유채박의 효소 가수분해물로 조제한 접착제를 사용한 합판의 접착특성 - 양인; Yang In; 한규성; Gyu Seong Han; 최인규; In Gyu Choi; 김용현; Yong Hyun Kim; 안세희; Sye Hee Ahn; 오세창; Sei Chang Oh (목재공학, 2012)
본 연구는 현재 사용되고 있는 석유화학계 접착제틀 대체하기 위하여 바이오 디젤 부산물인 유채박을 세 종류 (cellulase, pectinase, protease)의 효소를 단독 또는 조합하여 개량한 후 phenol formaldehyde (PF) prepolymer와 혼합하여 접착제를 제조하였으며, 이렇게 조제된 접착제를 적용시킨 합판의 접착능 및 포름알데히드 방산량을 조사함으로써 유채박의 합판용 접착제를 위한 원료화 가능성을 확인하고자 하였다. 유채박 접착제는 효소의 종류와 PF prepolymer의 몰비에 따라 6.26∼8.81의 pH와 2.980∼4.610 cps 점도를 보였으며, 고 형분 함량은 33% 내외인 것으로 조사되었다. 유채박 접착제로 제조된 합판의 접착능 및 포름알데히드 방산량을 조사한 결과, cellulase 또는 cellulase와 pectinase를 이용하여 순차적으로 가수분해한 유채박 가수분해물과 1.8-F/P.PF prepolymer로 조제한 접착제를 작용시킨 합판의 건조 및 준내수 인장강도가 가장 높았으며, 그 값 은 KS F 3101의 보통합판에 관한 최소 규정치인 0.6 N/mm2를 초과하는 것으로 나타났다. 한편 유채박 접착제로 제조된 합판의 포름알데히드 방산량은 전반적으로 1.0mg/&를 초과하지 않았으며, 대조구인 요소수지 접착제로 제조된 합판의 포름알데히드 방산량 (2.69 mg/&)과 비교하여 상당히 낮았다. 본 연구 결과로부터 유채박 접착제가 합판용 접착제로써 사용될 수 있다는 가능성을 제시할 수 있었으며, 유채박의 가수분해에 사용된 효소의 양 및 가수분해 시간을 조절하거나, 고형분 함량을 증가시켜 열압온도와 시간을 줄이는 방안 등이 유채박 접착제의 상용화를 위하여 향후 추가 연구가 되어야 할 것으로 생각한다. In the present study, rapeseed flour (RSF), which is a by-product from the production of edible oil and biodiesel extracted from rapeseed, was used to develop alternative adhesives for the production of plywood panels To examine the effects of the enzyme on the adhesive properties and formaldehyde emission of the RSF-based adhesive resins, three enzymes, such as cellulase (CEL), pectinase (PEC) and protease (ALC), were used either separately or together, As a crosslinking agent, PF prepolymers which were prepared with 15, 18 and 21.mole formaldehyde and I mol phenol (18-, 2.1- and 2.4-PF), were added into the RSF hydrolyzates. The adhesive resins formulated with GEL- or CEL-PEC-RSF hydrolyzates and 18-F/P PF prepolymers exhibited excellent adhesive strengths and formaldehyde emission The tensile shear strength and formaldehyde emission of the plywood panels bonded with the formulate resins were satisfied with the minimum requirement of the KS standard for ordinary plywood panels (0.6 N/mm2) In addition, formaldehyde emissions of the plywood panels approached to that of f0 specified in the KS standard (05 mg/I), and even had much better than those of commercial UP glue mixes. Overall, the use of RSF-based adhesive resins for the production of plywood panels might provide durable adhesive properties and an environmentally friendly substitute for petroleum-based adhesive resins However, further researches - the increase of solid content of RSF based adhesives for reducing press time and the microscopic observation of plywood specimen for identifying the relationship between tensile shear strength and the penetration of adhesives into wood structure -are required to commercialize the RSF-based adhesives.